Modeling of competitive distances qualified rowing and canoeing (illustrated man rowing) - Samuylenko, V. E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the study is to identify the best models of the race distance in rowing and canoeing. The study involved 12 highly skilled paddlers. Used heart rate monitors Polar RS800 G3, biochemical analyzer Dr. Lange LP-420. The possibility of individual simulations passage race distance. The factors that affect the distribution of forces on the distance. The optimal model of the passage of the 500 and 1000 meters. It was revealed that the distance of 200 meters has its own characteristics. The necessity of a separate simulation race distance in the non-Olympic rowing distances, length of more than 1000 meters. It is noted that in the competitive microcycle pay particular attention to the prelaunch workout consistent with the mobilization of the two leading mechanisms that ensure optimum energy supply at a distance. Recommended an increase in the volume of training loads in V (4b) intensity zone in the current control to monitor the index of hemoglobin, which should not significantly decrease.